An FDI is an FDI is an FDI? The growth effects of greenfield investment and mergers and acquisitions in developing countries - Philipp Harms; Pierre-Guillaume Méon (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We explore the effect of foreign direct investment (FDI) on economic growth in developing countries, distinguishing between mergers and acquisitions (M&As) and Greenfield investment. We find that these two types of FDI differ substantially with respect to their influence on growth. While Greenfield FDI substantially enhances growth, M&As have no effect, at best. We also demonstrate that, in contrast to Greenfield FDI, a larger volume of M&As results in an appreciated real exchange rate. The resulting loss in price competitiveness may explain the poor growth effect of the M&A variant of FDI.
Keywords: F21; F23; F43; O16; 330; Growth; foreign direct investment; mergers and acquisitions; green-field investments